Upaya Mahasiswa PAI Dalam Meningkatkan Kompetensi Menulis Naskah dan Public Speaking Sebagai Sarana Dakwah Prespektif Teori Need For Achievement - Imam Syafii; Nisfi Zulfatul Laili (Syntax Idea)
Two important skills that PAI students must possess to preach are writing and public speaking. This research has a purpose, namely to stimulate the interest of PAI students in the field of writing and public speaking as a means of dakwah. The method used in this research is a literature study, which will discuss the analysis of the skills of PAI students using the theory of Need for achievement. The results of this study explain that writing and public speaking are two skills that must be possessed by PAI students to support their achievements.